Cricket Match Outcome Prediction using Machine Learning Techniques - Dr.M .Baskar, Dr. J. Ramkumar, V.Venkateswara Reddy, G.Naveen Reddy (International Journal of Advanced Science and Technology, 2020)
Anticipating a game’s outcome has been recognized as a fundamental problem with the rise of numerical analysis of sports. Cricket has become one of the world’s best-recognized games. In this study suggested, It is a regulated technique to estimate from this group-built perspective the results of the one day Cricket match. This research demonstrates that somehow theviability of the squads between all the professional teams is an important predictor of the contender. Sculpting the overall team means sketching the efficiency of the overall batting and bowling strikers, this forms the foundation of the strategy offered. The professional stats and a player’s talent level to shape that as well. In terms of determining the result of a game, striker- independent variables were also taken into account. The algorithms used are Decision Tree, Logistic regression and Support Vector Classifier (SVC) yields better results in the experimentalevaluations.